Development of Ma'any Science Learning Materials Using the Language Style of the Al-Quran Al-Karim - Sangadji, Kapraja; Luhulima La Adu, Yusuf Abdulrahman (Peneliti.net, 2025)
The research aims to develop learning materials for the science of ma'any using the language style of the Al-Qur'an Al-Karim which can facilitate students to improve their abilities in the science of ma'asssny using the language style of the Al-Qur'an Karim. the concept of developing learning materials from a theoretical perspective of principles and procedures, then its development can be attempted practically starting from the activities of evaluating, adapting, completing, and compiling materials independently . Learning materials are everything that is used to help students practice the science of Ma'any using the language style of the Al-Qur'an . This study uses research and development (R and D). Qualitative data collection was carried out through interviews, observations, and documentation. and data analysis using Matthew & Huberman, through data reduction, presentation, drawing conclusions, and verification. While the questionnaire data was analyzed with quantitative analysis. The results of the study showed that the average presentation of the feasibility of the product of learning materials for Islamic sciences developed based on the validation test conducted by the four experts, with an average presentation of 90.56%, meaning that the product of learning materials for Islamic sciences for students that was developed was very suitable for use. The conclusion is that the results of the product of developing learning materials for Islamic sciences using the language style of the Al-Qur'an Al-Karim are very suitable for use by students.